2012
DOI: 10.1007/s00436-012-2907-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aqueous extract of Capsicum frutescens (Solanaceae) against the fish ectoparasite Ichthyophthirius multifiliis

Abstract: Abstracts Ichthyophthirius multifiliis is an important fish ectoparasite that often results in significant economic losses to freshwater aquaculture. The search of alternative substances to control infections of I. multifiliis became stringent after malachite green, an effective and widely used chemotherapeutant, is banned on fish farms because of its carcinogenicity and teratogenicity. In this study, the effects of the aqueous extract of Capsicum frutescens, which is readily available and affordable, were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 51 publications
3
29
0
1
Order By: Relevance
“…The result showed that tomonts were more resistant to the parasiticides than theronts. Similar results have also been noted in Ich treatment trials with other chemical (Buchmann et al, 2003) or plant extracts (Yi et al, 2012;Ling et al, 2012).…”
Section: Catfish Number/tanksupporting
confidence: 83%
See 2 more Smart Citations
“…The result showed that tomonts were more resistant to the parasiticides than theronts. Similar results have also been noted in Ich treatment trials with other chemical (Buchmann et al, 2003) or plant extracts (Yi et al, 2012;Ling et al, 2012).…”
Section: Catfish Number/tanksupporting
confidence: 83%
“…Therefore it is important to kill theronts in order to control ichthyophthiriasis. Reports in the literature indicated that theronts are more sensitive to plant-active parasitisides (Chu et al, 2010;Ling et al, 2012;Yi et al, Table 4 Results of prevention of Ich infestation on channel catfish by using the extract from G. chinesis at 15 days (mean ± SD of 3 tanks).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In general, chemical treatments may rapidly release poisonous and hazardous residuals with long degradation kinetics into water and soil ecosystems (Gholami‐Seyedkolaei et al., ; Yao et al., ). Moreover, there are other important problems in the use of chemicals to control ichthyophthiriasis in aquaculture systems such as low effectiveness, high cost, enhanced resistance of I. multifiliis to other antiparasitic compounds and also significant damage to the human health (Ling et al., , ; Sapkota et al., ; Tieman & Goodwin, ; Zhou, Liu, Zhang, Fu, & Lin, ). Therefore, there is a serious effort to reduce the use of these compounds or replace them with some eco‐friendly and safe compounds with natural origin to remove the contamination and infection caused by I. multifiliis in fish farms.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos com plantas do gênero Capsicum demonstram uma grande diversidade de metabólitos secundários, inclusive com ação inseticida e antifúngica (RIBEIRO & BEDENDO, 1999;LING et al, 2012;GUIMARÃES et al, 2014;VASCONCELOS et al, 2014). Apesar disto, há poucos estudos com Capsicum sobre o controle de fitopatógenos importantes economicamente.…”
unclassified